2017
DOI: 10.1128/jb.00253-17
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of the Lateral-Flagellar Genes of Bradyrhizobium diazoefficiens

Abstract: Bradyrhizobium diazoefficiens, a soybean N 2 -fixing symbiont, possesses a dual flagellar system comprising a constitutive subpolar flagellum and inducible lateral flagella. Here, we analyzed the genomic organization and biosynthetic regulation of the lateral-flagellar genes. We found that these genes are located in a single genomic cluster, organized in two monocistronic transcriptional units and three operons, one possibly containing an internal transcription start site. Among the monocistronic units is blr6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
13

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 69 publications
2
35
0
13
Order By: Relevance
“…In agreement with our previous observations ( Covelli et al, 2013 ; Mongiardini et al, 2017 ) and the results presented in Supplementary Figure S1B , we found the lateral-flagellar–filament structural flagellins Bll6865 and Bll6866, as well as the lateral-flagellar–hook protein Bll6858 in the AraDP ( Table 2 ), but we failed to detect the majority of the other lateral-flagellar components. Nevertheless, we recently found the transcripts for these proteins produced in the HMY-Ara but not in the HMY-Mtl, under the control of the lafR transcriptional regulator ( Mongiardini et al, 2017 ). Because flagellins and the flagellar-hook protein are the most abundant flagellar gene products, the lack of detection of the other proteins might have resulted from a low abundance or from a tight association with the flagellar structure that perhaps we did not manage to disassemble during the extraction.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In agreement with our previous observations ( Covelli et al, 2013 ; Mongiardini et al, 2017 ) and the results presented in Supplementary Figure S1B , we found the lateral-flagellar–filament structural flagellins Bll6865 and Bll6866, as well as the lateral-flagellar–hook protein Bll6858 in the AraDP ( Table 2 ), but we failed to detect the majority of the other lateral-flagellar components. Nevertheless, we recently found the transcripts for these proteins produced in the HMY-Ara but not in the HMY-Mtl, under the control of the lafR transcriptional regulator ( Mongiardini et al, 2017 ). Because flagellins and the flagellar-hook protein are the most abundant flagellar gene products, the lack of detection of the other proteins might have resulted from a low abundance or from a tight association with the flagellar structure that perhaps we did not manage to disassemble during the extraction.…”
Section: Resultssupporting
confidence: 93%
“…Since the amount of biomass produced per mole of ATP ( y x/ATP ) was the same for both culture conditions and the stoichiometric balances failed to reveal any substantial differences in the efficiency of ATP production per C-mole of substrate, the results would indicate that the cultures in the HMY-Ara consumed a larger proportion of the catabolic energy produced for simple maintenance—encompassing processes different from the production of biomass or C-products—than did those in the HMY-Mtl. One of these maintenance processes requiring energy may be the generation and use of the lateral flagella, which appendages are present in the HMY-Ara cultures but are scanty in the HMY-Mtl cultures ( Mongiardini et al, 2017 ; see also Supplementary Figure S1B ). To evaluate the contribution of the lateral flagella to qO 2max in HMY-Ara, we repeated the above measurements in both culture media with a B. diazoefficiens USDA 110 lafR ::Km insertional mutant lacking the class IB regulator of lateral-flagellum synthesis and therefore unable to produce any lateral flagellar structures, including the flagellar motor ( Mongiardini et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…B. diazoefficiens possesses a dual flagellar system with a constitutively expressed thick flagellum and several thin lateral flagella that are synthesized only in certain environmental conditions such as using arabinose as a carbon source, in a high-viscosity culture medium, or meeting obstacles in the swimming path. [44] Out of ≈40 genes known to be directly involved in flagellar structure and motor function in B. diazoefficiens, [45] 36 genes were upregulated by CeO 2 NPs and MWCNTs. However, the number of genes affected by ENMs in RE-supplemented media was lower than in minimal medium without RE (Figure 3).…”
Section: Mwcnts and Ceo 2 Nps Affected The Expression Of Genes Cruciamentioning
confidence: 99%